A scoping review of maternal and neonatal health services impacted during COVID-19 in Nepal - Gaire Sampada; Dilip Bhandari; Chika Yamamoto; Tianchen Zhao; Masaharu Tsubokura (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Coronavirus Disease 2019 (COVID-19), a global pandemic, has resulted in millions of deaths worldwide and severely impacted health service delivery systems. Developing countries, including Nepal, faced the risk of health system failure due to limited infrastructures. During the pandemic, Nepal experienced a decline in medical service utilization by pregnant women and a decrease in national child immunization rates. Maternity services and child immunization services had significant consequences, serving as a warning for future pandemics. This article examines the effects of pandemic-induced stay-at-home policies on maternal and child immunization in Nepal. # Methods A comprehensive literature search was conducted to identify relevant articles on PubMed, Scopus, and Google Scholar. The search terms employed were "maternal mortality in Nepal during COVID-19", "maternity service utilisation in Nepal during COVID-19", and "child immunisation in Nepal during COVID-19". The search was limited to articles published between 2019 and 2022, research conducted in Nepal, and that included maternal mortality, utilisation of maternity services, and child immunisation in the title of the full text. # Results Factors such as the closure of public transportation and service centres and fear of contamination contributed to a decline in antenatal care visits. The disruption of programs aimed at reducing the Maternal Mortality Rate (MMR) and decreased activities of Female Community Health workers in most parts of the country led to an increase in the maternal mortality rate during the stay-at-home policies. Institutional delivery decreased by 52.4% during the stay-at-home policies compared to the period before. The neonatal mortality rate increased from 13 to 40 per 1000 live births during the pandemic stay-at-home policies. Immunization centres were also closed in Nepal during the early stages of stay-at-home policies, with 50% of centres ceasing services. Measles outbreaks were reported in some parts of the country during the pandemic. # Conclusions To mitigate future damage, specific guidelines should be established based on regional factors and infrastructure development. Measures such as providing protective equipment and maintaining communication with pregnant women via telephone can help reduce the impact of future pandemics.